Talent development coaching: challenges and realities - McKeown, S.; Lyle, J. (International Sport Coaching Journal, 2025)
Academic literature has paid considerable attention to talent identification but much less to talent environments and the challenges facing sport coaches in such a domain. This paper provides insights into the challenges facing a coach in a resource-constrained environment, with goal ambiguity between immediate performance success and longer-term player development. Having identified prescriptions for good practice, the paper recounts the first author`s experience in attempting to accommodate conflicting goals and a novel performance model, within an Under-19 national volleyball squad. Particular attention is paid to recruitment, stakeholder perceptions, player commitment, a shared performance model across age groups, and longer-term player welfare. The paper concludes with a reminder that in such situations, coach support and welfare should also be a concern for sport federations.